Agriculture faculty students’ knowledge, attitude, and behaviors about genetically modified organisms (GMOs) (Annals of Medical Research, 2021)
Aim: This study was conducted in order to collect information about current knowledge, attitudes, and beliefs of students studying at Bingöl University Faculty of Agriculture regarding genetically modified organisms (GMOs) and to determine problems regarding the subject if any.Material and Methods: The population of this descriptive study consisted of students (146 students) studying at Bingol University Faculty of Agriculture. Data collection tool used in the study was the Questionnaire developed by the researchers based on literature information. Questionnaire consisted of 51 questions.Results: It was found that answers of students to the information on GMO were usually correct and their knowledge score on GMO was 4.9±1.2 out of 7. The rate of the students who found the production of genetically modified foods risky for all living creatures existing in the nature was 52.9% and 41.3% disapproved modifying genetics of foods to remedy hunger in the world. Conclusion: It was observed that the students had knowledge about the subject but they did not deem themselves to have sufficient knowledge hereof.